Numerical simulations of tests masonry walls from ceramic block using a detailed finite element model (Fracture and Structural Integrity, 2016)
This article deals with an analysis of the behaviour of brick ceramic walls. The behaviour of the walls was analysed experimentally in order to obtain their bearing capacity under static loading and their seismic resistance. Simultaneously, numerical simulations of the experiments were carried out in order to obtain additional information on the behaviour of masonry walls made of ceramic blocks. The results of the geometrically and materially nonlinear computations were compared to the results of the performed tests.
Keywords: Ceramic blocks; Mathematical model of a wall; Finite Element Method; Nonlinear computations